A dimensão pedagógica da religião: da pedagogia de Jesus à pedagogia cristã em tempos de sociedade secularizada. - Queiroz, Daniela Moura (2009)
This search tries to demonstrate the pedagogical dimension of religion in the practice of Jesus moviment. It was studied the link between pedagogy and religion, which involvers the development of the subject and the social construction. It was used as object the religions leader Jesus - public activity, method and teaching - , in order to understand his pedagogical practice in the first century in its historical context and to realize the implications of this practice in the discipleship and the pedagogical dimension of the Christian Religion in the current century. Therefore, the search also shows the pedagogical approaches in the ethical and realizing development of the subject, in which and pedagogy have influence in people s life and the Christian pedagogy answering to the secularized world. The methodology applied is from bibliographic form in an interdisciplinary perspective, in order to investigate the search in the area of Science of Religion, from the secular contribution of Bible studies. This, we hope to contribute with the discussion about how religion acts socially from pedagogical point of view.